Performance Analysis of Pseudolite Tropospheric Delay Models Using Radiosonde Meteorological Data - So, Hyoungmin; Park, Junpyo; Song, Kiwon (Journal of Positioning, Navigation, and Timing, 2013)
When pseudolite navigation system is applied to wide area, the tropospheric delay is the main error factor. In this study, we experimentally compared and analyzed the performance of the conventional pseudolite tropospheric delay models. The integration method using radiosonde meteorological data was suggested to derive the reference value for the comparison and analysis. Flight tests were carried out to analyze the performance of the tropospheric delay models according to the elevation angle and distance conditions between the user receiver and the pseudolite. As the results of this study, we provided the basis for the choice of tropospheric delay model appropriate to the relative location characteristics of the pseudolite and the user. KCI Citation Count: 2